Penerapan Metode Waterfall Dalam Pembuatan Aplikasi Administrasi Keuangan Sekolah Berbasis Website - Mushalifah, Siti Aisyah; Supriadi, Fidi; Junaedi, Dani Indra (Yayasan Pendidikan Tanggui Baimbaian, 2024)
Financial administration managemnet in educational insititutions is still mostly done in writing in an agenda book or cash book, which creates the risk of errors and data loss such as damager or loss. This approach to recording, which is still done in writing, carries the potential risk of loss or damage to the cash book, ehich can hamper validation between the student’s family and the school. This research develops a computer-based school financial administration application for Nu Darul Falah Middle School.development uses a waterfall method approach with stages of analysis, design, implementation, testing and maintenance. This application is created in the form of a website that allows usersto manage finacial transaction, payment arrangements and financial reports efficiently. Users can acces total and per class financial reports easily it is hoped that this application will increase efficiency, accuracy and transparency in school financial administration and speed up the process of preparing finacial reports